Synthesis of 4-Pyridinylquinolines via Sugasawa and Friedlander Reaction from 4-Cyanopyridine with Anilines and Ketones - Liu, Chi; Yang, Zhilin; Ji, Jiangyu; Li, He; Man, Lili; Li, Runlai; Zhang, Zhenming (Letters in Organic Chemistry, 2023)
Firstly, 2-amino aromatic ketones were synthesized by o-acylation of p-substituted anilines with nitrile under Sugasawa conditions, and the yield was up to 90.1%. Then, 4-pyridinylquinoline derivatives were synthesized by Friedlander reaction with α-methylene ketones, and the yield was up to 81.9%. The structures of five 2-amino aromatic ketones and eighteen substituted quinolines were characterized by MS, 1H NMR, and 13C NMR. The structures were further confirmed by single crystal X-ray diffraction, which was consistent with the expected structures. Analyzing the crystal structure, it was found that compounds 4j and 4q crystallized in the monoclinic with the P21/n space group, respectively. Compounds 2c, 2d, 2e, and 4n crystallized in the triclinic with the P-1 space group, respectively. Of which compound 4n crystallized in the triclinic space group P-1 with two crystallographically independent but chemically equivalent molecules in the asymmetric unit. The two independent molecules were found to possess different orientations of the chlorine, methyl, pyridyl, and acetyl groups relative to the core (quinoline) two-ring system. This work provides a simple, straightforward synthetic protocol for preparing 4-pyridinylquinoline derivatives.
Keywords: ketones